Association between sitting time and obesity: A population-based study in Peru - Paz-Krumdiek, Melissa (2020)
Aim: To assess if there is an association between sitting time and obesity among adult Peruvian population, using three different anthropometric measurements. Methods: A secondary analysis using data from a population-based study, the National Household Survey (ENAHO, in Spanish), was conducted enrolling adults aged ≥18 years from the 25 regions of Peru using a multistage random sampling technique. The outcome of interest was obesity, determined by body mass index (BMI > 30 kg/m2), waist circumference (WC > 80 and >90 cm in women and men, respectively) and waist to height ratio (WHR > 0.5); while the exposure was sitting time, measured using the last domain of the International Physical Activity Questionnaire and then categorised in <4 hours/day, 4 to <8 hours/day and 8+ hours/day. Associations were estimated using Poisson regression models, reporting prevalence ratios (PRs) and their respective 95% CI. Results: Data from 8587 subjects were analysed; mean age was 38.4 (SD: 13.5) and 53.6% were females. The prevalence of obesity was 16.3% (95% CI: 15.2–17.5%) by BMI, 58.5% (95% CI: 56.9–60.0%) by WC, and 78.0% (95% CI: 76.5–79.3%) by WHR. In the multivariable model, subjects reporting a sitting time of 8+ hours/day were more likely to be obese than those reporting <4 hours/day according to BMI (PR: 1.38; 95% CI: 1.15–1.65), WC (PR: 1.20; 95% CI: 1.12–1.28) and WHR (PR: 1.05; 95% CI: 1.01–1.10). Conclusions: Subjects with greater sitting time were more likely to be obese, and this association was evident with three different anthropometric indicators. Findings suggest the need of generating public health actions to reduce sedentary behaviour.